Utilizing of Code-Switching by Teacher in Teaching English at Grade XI MIA 1 SMAN 1 Sungai Penuh - Zaswita, Hermi (LPPM Universitas Jambi, 2018)
This research studied about how code-switching used by the teacher in classroom as alternative language in English subject. The subject of this research is one of teacher in SMAN 1 Sungai Penuh. The aim of this study were to analyze teacher’s language use in classroom by looking what kind of code that is chosen and what functions teacher do code-switching. The data was gained from videotape which recorded during English class. Based on data analysis of teacher’s script indicated that there are three kinds of language use in sentences: Pure English, Pure Indonesian and Mixing English-Indonesian. It was also obtained there are some functions of code-switching in teaching, namely, organizing the classroom inserting humor, clarifying information, increasing students' comprehension, and presenting the content of the material.